Stock market development and agricultural growth of emerging economies in Africa - Chi Aloysius Ngong; Kesuh Jude Thaddeus; Lionel Tembi Asah; Godwin Imo Ibe; Josaphat Uchechukwu Joe Onwumere (Journal of Capital Markets Studies (JCMS), 2022)
Purpose This research investigates the bond between stock market development and agricultural growth in African emerging economies from 1990 to 2020. Design/methodology/approach Agricultural value added to the gross domestic product measures agricultural growth and market capitalization and stock value traded measure stock market development. Findings The findings disclose that market capitalization negatively affects agricultural growth while stock value traded positively affects agricultural growth in the fully modified and dynamic ordinary least square techniques. The findings unveil bidirectional causality between labour and agricultural value added with unidirectional causality flow from agricultural value added to market capitalization and stock value traded. Research limitations/implications The governments should promote agricultural growth initiatives which stimulate stock market development. Effective methods required to encourage credit flow to the agricultural enterprises through the stock markets' intermediation should be promoted using aggressive policies which eliminate credit flow bottlenecks. Policy makers and regulatory authorities should implement policies which attract investors to the agricultural sector and encourage companies' listing in the stock markets. The capital market funding should be expanded to boost economic growth through agricultural value added. Originality/value Literature reveals divergent results on the relationship between stock market development and agricultural growth. Earlier studies provide conflicting findings on the bond between stock market development and agricultural growth. Some findings indicate positive link between stock market development and agricultural growth, while others show a negative association. Studies' results reveal opposing directions of causality between stock market development and agricultural growth.
Keywords: 330; Agricultural growth; DOLS; Emerging economy; FMOLS; Stock market